The Impact of Floods on Logistics Efficiency: A Case Study of Goods Delivery via Railway in Semarang City - Rusmansar, Yonathan Frista; Tohir, Muhammad (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
Flooding is a frequent natural disaster in Semarang City, significantly impacting the logistics sector. This study aims to analyze the impact of flooding on logistics efficiency in goods transportation using railways in Semarang City. The research employs a quantitative approach with secondary data analysis from railway operational reports and primary data through interviews with logistics actors and station managers. The findings reveal that flooding disrupts operations, causing delays, increased logistics costs, and reduced transport capacity. Additionally, access to railway stations is often hindered by water inundation, slowing down the distribution process. The study concludes that flooding significantly reduces logistics efficiency in Semarang City, particularly in railway transportation. To mitigate these impacts, robust infrastructure planning and improved coordination between logistics service providers and local governments are necessary.